Efficacy and Safety of Anti-malarial Drugs (Chloroquine and Hydroxy-Chloroquine) in Treatment of COVID-19 Infection: A Systematic Review and Meta-Analysis - Das, Rashmi Ranjan; Jaiswal, Nishant; Dev, Nishanth; Jaiswal, Nikita; Naik, Sushree Samiksha; Sankar, Jhuma (Frontiers in Medicine, 2020)
Background: Anti-malarial drugs inhibit coronaviruses in-vitro. Few published studies have evaluated the safety and efficacy of these drugs in treatment of COVID-19 infection. Materials & Methods: Systematic review and meta-analysis of clinical trials and observational studies. Major database searches were done till 5th June 2020. Participants admitted with RT-PCR confirmed SARS Cov-2 (COVID-19) infection were included. “Intervention group” received anti-malarial drugs with or without other drugs (Azithromycin) administered as an adjunct to the standard treatment/care. “Control group” received treatment except anti-malarial drugs. The primary outcome is “all-cause mortality”. Secondary outcome measures were effects on clinical and laboratory parameters, and adverse events. Results: Of 3472 citations, 17 (6 clinical trials, and 11 observational studies) studies provided data of 8071 participants. Compared to control, Hydroxy-chloroquine (HCQ) has no significant effect on mortality [(OR 0.87; 95% CI 0.46 to 1.64); 8 observational studies; N=5944]. Data from a single, small non-randomized trial (N=42) also reached similar conclusion (OR 1.94; 95% CI 0.07 to 50.57; p=0.69). Compared to control, HCQ plus Azithromycin (AZM) significantly increased mortality [(OR 2.84; 95% CI 2.19 to 3.69); 4 observational studies; N=2310]. Compared to control, risk of any adverse event was significantly increased in HCQ group [(OR 3.35; 95% CI 1.58 to 7.13); 4 clinical trials; N=263]. Compared to control, risk of adverse cardiac events (abnormal ECG, arrhythmia, or QT prolongation) were not significantly increased in HCQ group (but significantly increased in HCQ plus AZM group). The GRADE evidence generated for all the outcomes was of “very low-quality”. Conclusions: HCQ plus Azithromycin (not HCQ alone) increase mortality, and risk of adverse events. Due to “very low-quality” of evidence, caution should be taken while prescribing these drugs for treatment of COVID-19 infection at present.